Substance MCS-18 isolated from Helleborus purpurascens is a potent antagonist of the capsaicin receptor, TRPV1, in rat cultured sensory neurons - Neacsu, C; Ciobanu, C; Barbu, I; Toader, O; Szegli, G; Kerek, F; Babes, A (Physiological research, 2010)
Extracts of Helleborus roots were traditionally used in the Balkan area for their analgesic action. We report that the pure natural product MCS-18 isolated from this source is a potent, specific and reversible antagonist of the capsaicin receptor, TRPV1, expressed in rat dorsal root ganglion (DRG) neurons. TRPV1 is a non-selective cation channel expressed in a subset of cutaneous and visceral sensory nerve endings and activated by noxious heat, acidity and fatty acid metabolites of arachidonic acid, with a decisive role in inflammatory heat hyperalgesia. MCS-18 inhibited the increase in intracellular calcium concentration evoked in DRG neurons by capsaicin (300 nM) and low pH (5.5) but not by heat (43 degrees C). The substance had no effect on the responses mediated by acid-sensing ion channels (ASICs) or the irritant receptor TRPA1. Whole-cell patch-clamp was used to confirm the inhibition of capsaicin-induced currents by MCS-18 which was dose-dependent. The mechanism of inhibition does not require an intact cell, as capsaicin-induced currents were also inhibited in the excised outside-out configuration. The antagonism of the capsaicin and proton action on native TRPV1 by MCS-18 may be of interest for pain therapy.
Keywords: Calcium; bolest; Pain; kationtové kanály TRPV; vysoká teplota; Hot Temperature; Dose-Response Relationship, Drug; vápník; Patch-Clamp Techniques; krysa rodu Rattus; akrolein; spinální ganglia; Capsaicin; zvířata; Cells, Cultured; metoda terčíkového zámku; nervové receptory; Helleborus; kultivované buňky; Acids; Rats; kapsaicin; biologické přípravky; vztah mezi dávkou a účinkem léčiva; Animals; TRPV Cation Channels; Acrolein; Membrane Potentials; Sensory Receptor Cells; membránové potenciály; Ganglia, Spinal; Biological Products; kyseliny